DEVELOPMENT OF PUKIF (CREATIVE PUZZLE) LEARNING MEDIA FOR MADRASAH IBTIDAIYYAH STUDENTS - Citra Wahyu Mustika; Muhamad Ilman Nafi’an (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The development of PUKIF (Creative Puzle) learning media for Madrasah Ibtidaiyyah students can significantly improve learning outcomes and student engagement. However, it is still little developed for civic education learning in madrasah Ibtidaiyyah. . This study aims to develop the design and test the feasibility of PUKIF (Creative Puzzle) learning media. This research involved 29 students of class II-D MIN 1 Kota Kediri for the trial. This type of research and development in this study is using Research and Development (R&D) with the ADDIE model (Analyze, Design¸ Develop, Implement, and Evaluate). The instruments in this study are interviews, observations, documentation, questionnaires for material and media expert assessments, and student response questionnaires. The results showed that (1) the validation results of 2 media experts showed that the learning media was suitable for use in the learning process with an average score of 3.8 and 3.8 from the score range of 3.25 ≤ ¯x ≤ 4.00, While the results of the operational field trial show that the learning media is feasible to use in the learning process with an average score of 1.93, the score range is 1 < ¯x ≤ 2. For further research, researchers should compare the effectiveness of PUKIF with other existing learning media, such as flashcards, educational games, or other interactive learning methods.